Pneumocephalus Following Self-Inflicted Penetrating Brain Injury. (26th September 2017) - Ho, Che-Fang; Tam, Yuan-Yun; Wu, Chia-Chen
Abstract : Objective . Pneumocephalus is a rare complication that often occurs after traumatic skull base injury, leading to morbidity and mortality. Material and Method . We present the case of a 42-year-old healthy man who injured himself when he stuck a metal stick into his left nasal cavity to relieve prolonged nasal obstruction. Immediate cerebrospinal fluid rhinorrhea and subsequent meningitis and pneumocephalus occurred later. He was presented at our hospital with fever and meningeal signs. Result . Computed tomography scans revealed left rhinosinusitis and air collection in the subarachnoid space. The patient received the conservative treatment of bed rest, intravenous hydration, head elevation, and broad-spectrum intravenous antibiotics. Pneumocephalus and meningitis resolved without any surgery, and he experienced no other sequela or complication . Conclusion . Pneumocephalus is a rare incidence and can lead to high morbidity and mortality. Prompt diagnosis and adequate treatment of pneumocephalus and meningitis proved beneficial for our patient who recovered without any complication or surgery.